SÍNTESE, AVALIAÇÃO ESTRUTURAL, PROPRIEDADES FOTOFÍSICAS E BIOATIVIDADE DE COMPOSTOS DE COORDENAÇÃO DE CÁDMIO (II) COM LIGANTES DERIVADOS DE ÁCIDOS PIRIDINO-DICARBOXÍLICOS - Débora Taisa Keller da Silva (2022)
This study has produced the synthesis, characterization, and the biological application of two new complexes from the pyridine 2,5-dicarboxylate acid (ligands 1) and 2,2-bipiridyne (Bipy) with the íon Cd(II). The synthesis of the complex (1) is realized through ligands (1) which coordinates with íon Cd(II) forming the complex (1). The complex (2) is formed in two steps, in the first one the associate (Bipy) connect itself to the metalic center forming a synthetic intermediate that is subsenquently reacted “in situ” with ligands (1), which coordinates with the metal íon forming the complex (2). The synthethized complexes belong to the triclinic cristaline system with a P-1 spatial group. Both complexes showed distorted octahedral geometry. FTIR, 1H and 13C NMR analyzes were performed, and it was possible to observe that the ligands effectively coordinated the metallic center, confirming the formation of two new Cd(II) complexes. These structures were confirmed by X-ray diffraction in monocrystals and characterized by techniques involving mass spectrometry, absorption spectroscopy in the infrared region, and absorption spectroscopy in the UV-visible region, elemental analysis of CHN. Molecular orbital calculations were performed using the Time Dependent Functional Density Theory method (TD-DFT) to assist in the interpretation of eletronic transitions observed in the molecular absorption spectroscopy (UV-Vis), mixed electronic transitions of the MLCT type (charge transfer from metal to ligands) with IL (Intraligands) and LMCT (charfe transfer from ligands to metal) with IL (intraligands) and finally tests of biological activity agains Candida albicans (ATCC 90028), Candida tropicalis (ATCC 750), Candida krusei (ATCC 6558) and Candida glabrata (ATCC 2001), Where it demonstrated excelente minimal inhibitory concentration (MIC) activity in the Candida krusei strain. Both synthethized complexed presented attractives properties in relation to potencial applications, both in materials science and in the prospection of new bioactives molecules.